Service Quality Evaluation in a Telecommunication Service Provider - Nurwulan, Nurul Retno; Almansoori, Muzna Dhaiban Mohamed Dhaiban; Alhammadi, Salma Abdulla Mohamed Abdulla; Alhosani, Mohamed Khaleel Ahmed Ibrahim; Alhammadi, Hamad Mohamed Ahmed Marei (Equator Journal of Management and Entrepreneurship (EJME), 2026)
This study evaluates service quality in a telecommunications service provider by identifying factors that influence customer satisfaction and retention. Using the SERVQUAL framework, the research assesses network reliability, service responsiveness, pricing perceptions, and customer support efficiency through a survey of 150 users supported by a literature review. Frequency analysis, correlation analysis, and regression modeling were applied to determine major service quality gaps. Results show that network reliability is the most critical concern: 36.7% of respondents experience frequent connectivity problems, while 26.7% report occasional interruptions. Customer service performance presents additional challenges, with 29.3% receiving no response to complaints and 26.7% facing service outages lasting more than a day. Perceived value for money significantly affects customer satisfaction and 23.3% of users report dissatisfaction with the service’s value. A notable 32.7% of respondents indicate intentions to switch providers, suggesting substantial retention risks. The findings highlight the need for AI-enabled customer service improvements, network infrastructure upgrades, and more competitive pricing strategies to enhance dependability and strengthen customer value perceptions. The study confirms that the SERVQUAL dimensions of reliability, responsiveness, and assurance are the strongest predictors of satisfaction, aligning with existing research. To maintain competitiveness, the priority should be in developing enhanced digital service platforms, improving customer engagement processes, and optimizing pricing structures to better meet user expectations.